Appraisal of Farm Diversification and Livelihood System of Bihar (India) - Singh, Neha; Kadian, K. S.; Raj, Khusboo; Meena, H. R. (Indian Journal of Extension Education, 2023)
The paper examines state-level trends in Bihar for determining patterns in farm diversification for the period 1990-91 to 2018-19, using the Simpson Index of Diversification (SID) and ordinal linear regression analysis to analyse the determinants. The study, conducted in the year 2022, reported that the cropping system at the state level is transforming from food grains to different high-value crops and allied farming sectors. The transformation was not uniform across the regions. The SID values have demonstrated how the agricultural economy has been more diverse over time, with some variations in the production of food and non-food crops. The result of multiple regressions has revealed earning members, social work participation, and government donations to be the major determinants of farm diversification, and various constraints were identified using the Garrett ranking method. Hence, the study suggests that policy support for the development of dairy farmers should be more focused on increased cropping intensity, insurance protection, investments in agricultural research and education, and technology development.